Barriers and facilitators of health behavior engagement in ultra-Orthodox Jewish women in Israel. (13th November 2019) - Leiter, E; Finkelstein, A; Greenberg, K; Keidar, O; Donchin, M; Zwas, D R
Abstract: Background: The ultra-Orthodox Jewish (UOJ) community is a primarily low socio-economic, culturally insular minority sub-sect in Israel. Compared with the general population, UOJ women report higher rates of diabetes and overweight, lower physical activity rates, and have lower breast cancer survival rates. Research in this sub-sect is limited. Identifying the facilitators and barriers to health behavior engagement would facilitate public health intervention design in this population. Methods: This study describes UOJ women's barriers and facilitators to engagement in targeted health behaviors (i.e. health nutrition, physical activity), identified through mixed methods analysis. Qualitative and quantitative analyses of interviews (N = 5), focus groups (5, including 35 women), and questionnaires (N = 239) identified barriers to engaging in preventive health behaviors and intervention preferences. Results: Most of the barriers identified (financial and time limitations, personal preferences, lack of education/awareness, and family-related obstacles) are similar to those reported by women from the general population. Cultural aspects such as women's role in the home, religious restrictions, and modesty were also identified as barriers to health behavior engagement, comparable to women from other insular communities. Conclusions: Utilizing a mixed methods approach in identifying barriers and facilitators informed intervention development and improved cultural tailoring, potentially serving as a model for intervention design with additional UOJ communities as well as other difficult to access, low socio-economic, culturally insular populations. Key messages: This is the first study identifying facilitators and barriers to UOJ women's health behavior engagement. Findings can inform intervention design in difficult to access, culturally insular populations.